SHORT INTRODUCTION TO ETHICAL REASONING IN SPORT - Milan Hosta (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
It is clear at fi rst sight that sport is a very complex phenomenon, which generates ethical contradictions. It is pinned between moral-educational and essential biological movement drives on the one side. On the other side, it is trapped between extreme exploitation and passionate images of our time, and playful innocence of body and mind. By justifying ethical pluralism through our discussion we wish to point out that moral pluralism is not an apology for moral relativism, which can also be labeled as an ethical void. Moral autonomy of sport that is based on the idea of free pooling of civil society, and is at the same time trapped in the structure of the game, is inadmissible per se or has to be understood within the context of distinction among ethics of sport and sport ethics. Since we are dealing with pluralism, we cannot assure in advance the expected convincing power of ethical reasoning in sport. It is not uniform phenomenon and therefore such a demand would be too pretentious. However, as a PE teachers and trainers we need to stand fi rm on ethical grounds. We need to take into account that this short introduction is only a fi rst stage of understanding sport in order to develop further educational strategies to promote and practice socially responsible sport in the 21st century.